Predictors of Active Aging Among Community-dwelling Older Adults in Qazvin City, Iran, 2023 - Zahra Shirshekan; Ahad Alizadeh; Mohammad Amerzadeh; Fatemeh Mohammadi; Seyedeh Ameneh Motalebi (Iranian Rehabilitation Journal)
Objectives: This study aims to determine the predictive factors of active aging among older people in Qazvin City, Iran. Methods: This study, conducted in 2023, included individuals aged >60 years in Qazvin City. Participants were selected using cluster sampling in three zones of Qazvin City. Older adults were selected from mosques and parks in each zone. Data were collected using a demographic information checklist, an Iranian active aging questionnaire, a multidimensional scale of perceived social support (MSPSS) and the World Health Organization (WHO) disability assessment schedule (WHODAS 2.0). A multiple linear regression was performed using R software, version 4.2.3 to detect predictors of active aging. Results: The mean age of the patients was 66.78±6.22 years. A total of 178 patients (61.6%) were men and 207(71.6%) were married. The mean score for active aging was 109.18±24.15, indicating a moderate level. Multiple regression analysis showed that sex, marital status, educational level, economic situation, job, perceived health, disability and perceived social support were significant predictors of active aging Discussion: Based on our results, active aging among older adults was moderate. We suggest that health policymakers pay more attention to older individuals with low literacy, low income, disabilities, and health problems when planning active aging programs. Additionally, increasing intergenerational support is vital to encourage social participation among older adults.